2017
DOI: 10.1038/bjc.2017.301
|View full text |Cite
|
Sign up to set email alerts
|

Separase is a marker for prognosis and mitotic activity in breast cancer

Abstract: Background:Cancer cell proliferation is a critical feature in classifying and predicting the outcome of breast carcinoma. Separase has a central role in cell cycle progression in unleashing sister-chromatids at anaphase onset. Abnormally functioning separase is known to lead to chromosomal instability.Methods:The study comprises 349 breast carcinoma patients treated in Central Hospital of Central Finland. The prognostic value, role as a proliferation marker and regulatory interactions of separase are evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…In order to investigate the mechanism of anticryptosporidial activity we evaluated expression proliferation (separine) and apoptosis markers (metacaspase) in the parasite. We observed a down regulation in separine expression (also known as separase) which is implicated chromatin regulation during meiosis and mitosis processes 24 , this finding suggest that EA may be blocking proliferation through NDK inhibition as observed in silencing experiments, however also we observed an up regulation of metacaspase which suggest that other mechanisms may be involved in parasite killing. EA has showed multiple benefits to human health trough enhancement of immune system or epithelial barrier 25-27 , thus we speculate that EA has a dual effect on Cryptosporidium by reducing the infection trough the activation of host pathways (e.g.…”
Section: Discussionsupporting
confidence: 66%
“…In order to investigate the mechanism of anticryptosporidial activity we evaluated expression proliferation (separine) and apoptosis markers (metacaspase) in the parasite. We observed a down regulation in separine expression (also known as separase) which is implicated chromatin regulation during meiosis and mitosis processes 24 , this finding suggest that EA may be blocking proliferation through NDK inhibition as observed in silencing experiments, however also we observed an up regulation of metacaspase which suggest that other mechanisms may be involved in parasite killing. EA has showed multiple benefits to human health trough enhancement of immune system or epithelial barrier 25-27 , thus we speculate that EA has a dual effect on Cryptosporidium by reducing the infection trough the activation of host pathways (e.g.…”
Section: Discussionsupporting
confidence: 66%
“…In bonobos, five of these genes are, according to the literature, involved in female reproduction: ABCA13 (Nymoen et al. 2015), ESPL1 (Gurvits et al. 2017), KIF14 (Singel et al.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the mechanism of anticryptosporidial activity, we evaluated expression proliferation (separine) and apoptosis markers (metacaspase) in the parasite. We found a down-regulation of separine expression (also known as separase), which is implicated in chromatin regulation during meiosis and mitosis processes 27 . This finding suggested that EA may be blocking proliferation through NDK inhibition, as found in the silencing experiments.…”
Section: Discussionmentioning
confidence: 82%